COVID-19 PANDEMIC-INDUCED STRESS STORM IN DIFFERENT SOCIETIES - Nang Thinn Thinn Htike; Rehanna Mansor; Jannathul Firdous (Asian Journal of Medicine & Health Sciences, 2020)
The corona virus infection originated in Wuhan, China and then developed into global pandemic crisis. This crisis created stress, fear, anxiety, uncertainty which lead to a resilience testing of mankind in 21st centuries. This review aimed to highlight the scientifically determined psychological stress and biological stress that happened in various populations with different social norms. The online database was systematically searched from PubMed, Google Scholar and Elsevier COVID-19 information center. The result yield 42 citations and literature review was performed. The evidence proved that COVID-19 pandemic induced unstable psychological conditions such as anxiety, depression, post-traumatic stress disorders in patients, health care workers, the general population, and vulnerable populations like women, children, elderly, business dealers and migrant workers though the intensity of suffering was different among individuals. Apart from psychological stress, COVID-19 infection induced the biological stress by promoting oxidative stress and cortisol secretion which adversely affect the survival of patients. This review emphasized that one should be aware of the stress storm created by this pandemic situation and be prepared for further management.